Molecular disruption of neuroinflammatory and metabolic pathways mediates triclosan-induced depressive-like behavior in zebrafish - Danting Wang; Junping Liu; Ruixue Zhou; Bing Han; Chunxia Chen; Wentong Meng; Li Qin; Limei Sun; Bin Tan; Chunyan Huang (Toxicology and Applied Pharmacology, 2026)

Thermodynamic Simulation of Heavy-Metal Transformation During Municipal Sludge Incineration Process - Junping Meng; Junwei Shen; Chandrasekar Srinivasakannan; Jinsheng Liang; Xinhui Duan (Water, Air, & Soil Pollution, 2026)

Corrigendum to ‘Magnetic biochar prepared by co-pyrolysis of sludge and organic medical solid waste for pH-universal removal of ciprofloxacin’ [Journal of Contaminant Hydrology 277 (2026) 104862] - Junping Meng; Binbin Yao; Jinsheng Liang; Xinhui Duan; Xiangying Wei (Journal of Contaminant Hydrology, 2026)

Magnetic biochar prepared by co-pyrolysis of sludge and organic medical solid waste for pH-universal removal of ciprofloxacin - Junping Meng; Binbin Yao; Jinsheng Liang; Xinhui Duan; Xiangying Wei (Journal of Contaminant Hydrology, 2026)

Study of supercooling phenomena in soil-water systems based on nucleation theory: quantifying supercooling duration - Kunyu Li; Chong Wang; Ying Lai; Jiaqi Tian; Fanshuo Meng; Junping Ren; Shuangyang Li (Cold Regions Science and Technology, 2026)

Influence of hydraulic fluctuations on the microstructure and mechanical properties of coal - Yiyu Lu; Shipu Miao; Zhaohui Lu; Junping Zhou; Baixue Wang; Jiankun Zhou; Shirong Meng (Gas Science and Engineering, 2025)

Adsorption of weak polar zearalenone mycotoxins from water environment by tourmaline mineral powder of spontaneous electrical polarization properties - Na Zhang; Xiaoyu Han; Yinyuan Lei; Junping Meng; Hong Zhang; Jinsheng Liang (Environmental Research, 2025)

Co-combustion of organic medical solid waste and municipal sewage sludge: Combustion characteristics and gaseous pollutant emissions - Junwei Shen; Junping Meng; Binbin Yao; Jinsheng Liang (Journal of Environmental Chemical Engineering, 2025)

Co-exposure to triclosan and polystyrene nanoplastics on neurodevelopmental toxicity and gut microbiota dysbiosis in zebrafish (Danio rerio) - Danting Wang; Junying Lan; Wentong Meng; Junping Liu; Ruixue Zhou; Chunxia Chen; Li Qin; Bin Tan; Chunyan Huang (Environmental Pollution, 2025)

Two nuclear loci Rf-m1 and Rf-m2 interplay to determine the fertility restoring efficacy of ZD-type CMS soybean - Xiaoxia Yu; Yupeng Feng; Lulu Zhou; Hongye Gao; Hongbin Wang; Yaru Chen; Jiamai Liang; Tianyu Meng; Meng Li; Yihan Yuan; Junping Yu; Hao Liu; et al. (Theoretical and Applied Genetics, 2025)

Highly efficient recovery of Zn (II) from zinc-containing wastewater by tourmaline tailings geopolymers to in-situ construct nanoscale ZnS for the photodegradation of tetracycline hydrochloride - Zhixiao Ren; Caihong Zhang; Jinpeng Chen; Hong Zhang; Junping Meng; Xiaoyu Han; Jinsheng Liang (Environmental Research, 2024)

Predicting frost heave in soil-water systems using the generalized regression neural network optimized with particle swarm optimization algorithm - Honghong Cai; Chong Wang; Ziqiang Ma; Fanshuo Meng; Zhikun Lin; Junping Ren; Shuangyang Li (Cold Regions Science and Technology, 2024)

Craniocervical Manual Lymphatic Drainage Increases the Efficiency of Atorvastatin-Based Treatment of Chronic Subdural Hematoma - Chuang Gao; Yingsheng Wei; Xinjie Zhang; Jinhao Huang; Meng Nie; Xuanhui Liu; Jiangyuan Yuan; Dong Wang; Ye Tian; Weiwei Jiang; Shuo An; Jian Sun; et al. (Translational Stroke Research, 2023)

Experimental Characteristics of Hydrocarbon Generation from Scandinavian Alum Shale Carbonate Nodules: Implications for Hydrocarbon Generation from Majiagou Formation Marine Carbonates in China’s Ordos Basin - Yiqing Wang; Yaohui Xu; Junping Huang; Jianglong Shi; Heng Zhao; Qingtao Wang; Qiang Meng (Journal of Marine Science and Engineering, 2023)
The hydrocarbon source rocks of the marine carbonates of the Ordovician Majiagou Formation in the Ordos Basin are generally in the high-overmature stage and are, therefore, not suitable for hydrocarbon thermal simulation experiments. Their hydrocarbon generation potential and hydrocarbon generation characteristics are not clearly understood. Meanwhile, Nordic Cambrian carbonates are similar in lithology, parent material type, and sedimentary age, and are in the low evolution stage, which is suitable for hydrocarbon thermal simulation experiments. Therefore, in this study, we selected the Nordic carbonates for the gold tube thermal simulation experiment to analyze the content and geochemical characteristics of the thermal simulation products. The experimental results are also compared and analyzed with the characteristics of thermal simulation products of Pingliang Formation mud shale (contemporaneous with the Majiagou Formation) and Shanxi Formation coal (in the upper part of the Majiagou Formation), which are similar to the Majiagou Formation in the Ordos Basin. The results showed that the Nordic carbonate has different hydrocarbon production characteristics from the mud shale of the Pingliang Formation of the same parent material type, and although the hydrocarbon production yields of the two are not very different, the carbonate still produces methane at 600 °C. The hydrocarbon production yield of the Nordic carbonates is almost equivalent to that of type-II2 kerogen, indicating that the hydrocarbon production yield is not related to lithology and only to the organic matter type; however, the Nordic carbonate can produce a large amount of H2S. The alkane carbon isotope changes are mainly controlled by the degree of thermal evolution, showing gradual heaviness with increasing temperature. No carbon isotope sequence reversal occurred during the thermal simulation, and its distribution range is roughly the same as that of the alkane carbon isotope composition of the mud shale of the Pingliang Formation. The ethane carbon isotope composition is as heavy as −21.2‰ at the high-temperature stage, showing similar coal-type gas characteristics. The addition of calcium sulphate (CaSO4) causes the TSR reaction to occur, which has a significant impact on the methane content under high maturity conditions, reducing its content by more than 50% at 600 °C. However, the addition of CaSO4 increases the yield of heavy hydrocarbon gases, such as ethane, and promotes the production of C6-14 hydrocarbons and C14+ hydrocarbons at high-temperature stages, and the addition of CaSO4 substantially increases the yield of H2, CO2, and H2S. The thermal simulation results have implications for the hydrocarbon formation mechanism of the early Paleozoic marine carbonate formation system in the stacked basins of the Ordos Basin and the Tarim Basin in China.

Immune-Ageing Evaluation of Peripheral T and NK Lymphocyte Subsets in Chinese Healthy Adults - Zhenghu Jia; Zhiyao Ren; Dongmei Ye; Jiawei Li; Yan Xu; Hui Liu; Ziyu Meng; Chengmao Yang; Xiaqi Chen; Xinru Mao; Xueli Luo; Zhe Yang; et al. (Phenomics, 2023)
Ageing is often accompanied with a decline in immune system function, resulting in immune ageing. Numerous studies have focussed on the changes in different lymphocyte subsets in diseases and immunosenescence. The change in immune phenotype is a key indication of the diseased or healthy status. However, the changes in lymphocyte number and phenotype brought about by ageing have not been comprehensively analysed. Here, we analysed T and natural killer (NK) cell subsets, the phenotype and cell differentiation states in 43,096 healthy individuals, aged 20–88 years, without known diseases. Thirty-six immune parameters were analysed and the reference ranges of these subsets were established in different age groups divided into 5-year intervals. The data were subjected to random forest machine learning for immune-ageing modelling and confirmed using the neural network analysis. Our initial analysis and machine modelling prediction showed that naïve T cells decreased with ageing, whereas central memory T cells (Tcm) and effector memory T cells (Tem) increased cluster of differentiation (CD) 28-associated T cells. This is the largest study to investigate the correlation between age and immune cell function in a Chinese population, and provides insightful differences, suggesting that healthy adults might be considerably influenced by age and sex. The age of a person's immune system might be different from their chronological age. Our immune-ageing modelling study is one of the largest studies to provide insights into ‘immune-age’ rather than ‘biological-age’. Through machine learning, we identified immune factors influencing the most through ageing and built a model for immune-ageing prediction. Our research not only reveals the impact of age on immune parameter differences within the Chinese population, but also provides new insights for monitoring and preventing some diseases in clinical practice.

Recycling of iron ore tailings into magnetic nanoparticles and nanoporous materials for the remediation of water, air and soil: a review - Xiaoyu Han; Fei Wang; Yan Zhao; Junping Meng; Guangyan Tian; Lijuan Wang; Jinsheng Liang (Environmental Chemistry Letters, 2023)

QTL Mapping of Growth Traits in Yellow River Carp (Cyprinus carpio haematopterus) at 5–17 Months after Hatching - Yuhan Chen; Jintai Huang; Zhan Jin; Junping Chen; Meng Zhang; Miao Yu; Hongxia Jiang; Lei Wang; Zhigang Qiao (Fishes, 2023)
To screen the quantitative trait loci (QTL) and genes related to the growth of Yellow River carp (Cyprinus carpio haematopterus) after removing the maternal effect, we established a family of these carps. Four growth-related traits (body length, height, thickness, and weight) of the family at 5 and 17 months after hatching (MAH) were measured. Analysis of QTL mapping for the four growth-related traits was conducted using the genetic linkage map constructed in our laboratory. We identified 47 QTL that were related to the four growth traits and three consensus QTL (cQTL). A total of 10, 14, 10, and 13 QTL were associated with body length, height, thickness, and weight, respectively; cQTL-1, cQTL-2, and cQTL-3 contained 11, 2, and 2 QTL, respectively. We detected 17 growth-related candidate genes within 50 Kb upstream and downstream of the five main-effect QTL (phenotypic variation explained > 10%, logarithm of odds > 5.5). Two genes (cbfa2t2 and neca1) that may be affected by maternal effects were identified by comparing the main-effect QTL at 17 and 5–17 MAH. This study was the first attempt to eliminate growth-related QTL and genes affected by maternal effects in Yellow River carp. These results can be used in molecular marker-assisted breeding and provide valuable genomic resources for the genetic mechanisms underlying growth in Yellow River carp.

Efficient polysulfides trapping and redox enabled by Co/N-carbon implanted Li+-montmorillonite for advanced lithium-sulfur batteries - Yanfei Yang; Guilin Meng; Hongli Wang; Wankai Wang; Junping Zhang (Chemical Engineering Journal, 2023)

Mapping Growth-Related Quantitative Trait Locus (QTL) in Commercial Yellow River Carp (Cyprinus carpio haematopterus) during Overwintering - Lei Wang; Lan Zhang; Yuhan Chen; Junping Chen; Meng Zhang; Miao Yu; Hongxia Jiang; Zhigang Qiao; Xuejun Li (Fishes, 2022)
The common carp (Cyprinus carpio) is farmed globally; as a subspecies, the Yellow River carp (C. c. haematopterus) is widely farmed in northern China. Since the Yellow River carp grows slowly in winter, it would benefit breeders to implement a breeding program targeting growth in winter. In May 2017, we established a Yellow River carp family and measured the body length, height, thickness, and weight of individuals before (October 2017) and after winter (February 2018). Based on the genetic linkage map established in our laboratory, the quantitative trait locus (QTL) mapping of these four traits led to the detection of 29 growth-related QTLs, of which 9, 7, 3, and 10 QTLs were associated with body length, height, thickness, and body weight, respectively. One consensus QTL contained seven QTLs associated with four traits. Through the two major-effect QTLs (qBL-p-1 and qBL-p-2), we screened three candidate genes (fnd3b, ghsr, and pld1), which were associated with biological activities, such as fat formation, growth, and membrane transport. These results are helpful in exploring the growth regulation mechanism and providing a reference for genetic breeding with regard to the overwintering growth of Yellow River carp.

Broadcast ephemerides for LEO augmentation satellites based on nonsingular elements - Lingdong Meng; Junping Chen; Jiexian Wang; Yize Zhang (GPS Solutions, 2021)

Performance of BDS-3: satellite visibility and dilution of precision - Minghua Wang; Jiexian Wang; Danan Dong; Lingdong Meng; Junping Chen; Ahao Wang; Haomeng Cui (GPS Solutions, 2019)

Astragalus polysaccharides inhibits cell growth and pro-inflammatory response in IL-1β-stimulated fibroblast-like synoviocytes by enhancement of autophagy via PI3K/AKT/mTOR inhibition - Qingliang Meng; Xuzhao Du; Huilian Wang; Huimin Gu; Junping Zhan; Zipeng Zhou (Apoptosis, 2017)

IL-22 Impedes the Proliferation of Schwann cells: Transcriptome Sequencing and Bioinformatics Analysis - Shengming Xu; Junping Ao; Haihui Gu; Xiaoqing Wang; Chong Xie; Depeng Meng; Lishan Wang; Mingyuan Liu (Molecular Neurobiology, 2017)

Responses of rose RhACS1 and RhACS2 promoters to abiotic stresses in transgenic Arabidopsis thaliana - Muhammad Ali Khan; Yonglu Meng; Daofeng Liu; Hongshu Tang; Suhui Lü; Muhammad Imtiaz; Guimei Jiang; Peitao Lü; Yuqi Ji; Junping Gao; Nan Ma (Plant Cell Reports, 2015)